Monitoring and Improving Sleep Quality in Professional Athletes - Marcelina Guzik; Zuzanna Wyleciał; Patryk Dąbrowski; Julia Ząber (Quality in Sport)
Introduction and Purpose: Sleep is a fundamental component of performance, recovery, and overall health in professional athletes. However, sleep disturbances—including insufficient duration, poor quality, and insomnia—are highly prevalent in this population due to factors such as early-morning training, late-evening competitions, transmeridian travel, and psychological stress. This review aims to provide a comprehensive summary of current knowledge regarding sleep monitoring techniques and evidence-based interventions to improve sleep in elite athletes.